Clinical Significance of IgM and C3 Glomerular Deposition in Primary Focal Segmental Glomerulosclerosis - Zhang, Yi-miao (Clin J Am Soc Nephrol, 2016)
BACKGROUND AND OBJECTIVES: Glomerular IgM deposition is commonly shown in primary FSGS and sometimes accompanied by C3 deposition. Clinical presentation and treatment outcomes of these patients are not investigated in detail. DESIGN, SETTING, PARTICIPANTS, &MEASUREMENTS: One hundred six consecutive patients with biopsy–proven primary FSGS from 2004 to 2014 were enrolled retrospectively. Clinical features and treatment outcomes were compared between patients with and without IgM/C3 deposition. RESULTS: Fifty-eight (54.7%) patients presented with IgM glomerular deposition on sclerotic segments. C3 and C1q depositions were shown exclusively in patients with IgM deposition (34.5% versus 0.0%; P<0.001 and 8.6% versus 0.0%; P=0.04, respectively). Patients with IgM deposition were younger (median; range: 24.5; 18.8–39.0 versus 46.5; 26.0–64.0 years old; P=0.001), had higher level of serum IgM (142.5; 96.3–206.0 versus 107.0; 71.0–140.0 mg/dl; P=0.01), and had higher level of eGFR (median; range 97.7; 48.0–135.8 versus 62.1; 33.7–93.9 ml/min per 1.73 m(2); P=0.01) at the time of kidney biopsy. The percentage of sclerosis lesions was significantly higher in patients with C3 deposition (median; range: 21.7%; 15.3%–31.1% versus 9.2%; 6.6%–20.0%; P=0.002). Although patients received comparable immunosuppressive treatments during 58.9 (29.5–81.1) months of follow-up, a significantly higher prevalence of refractory cases (no response or steroid dependent) occurred in patients with combined IgM and C3 deposition compared with patients with IgM deposition alone or without IgM deposition (58.8% versus 22.2% versus 15.6%, respectively; P=0.004). Multivariate analysis identified combined IgM and C3 deposition (odds ratio, 11.32; 95% confidence interval, 2.26 to 56.65; P=0.003) as an independent risk factor for refractory patients; 19 of 98 patients developed renal dysfunction when their serum creatinine levels increased >30% from baseline and reached >1.5 mg/dl. Combined IgM and C3 deposition (hazard ratio, 5.67; 95% confidence interval, 1.34 to 23.84; P=0.02) was identified as an independent risk factor for renal dysfunction. CONCLUSIONS: Patients with primary FSGS and IgM and C3 deposition showed unfavorable therapeutic responses and worse renal outcomes, which indicate that IgM and C3 deposition might involve disease progression via complement activation.